Woody plant composition along Ulot River, Samar Island Natural Park, Philippines: Community uses and conservation concerns - ANNE FRANCES V. BUHAY; MARIA CELESTE N. BANATICLA-HILARIO; INOCENCIO E. BUOT JR; JONES T. NAPALDET; LAILANI MASUNGSONG; MARNE ORIGENES; NOBA HILVANO; EDELYN ECHAPARE; DIANE SHANE BALINDO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Buhay AFV, Banaticla-Hilario MCN, Buot Jr IE, Napaldet JT, Masungsong L, Origenes M, Hilvano N, Echapare E, Balindo DS. 2025. Woody plant composition along Ulot River, Samar Island Natural Park, Philippines: Community uses and conservation concerns. Biodiversitas 26: 3081-3103. A comprehensive woody plants inventory is crucial for local governments and agencies to determine useful plant species and develop effective conservation policies. This study enumerates woody plant species in the Ulot riparian forest of Samar Island Natural Park (SINP), Philippines. A total of 574 individual plants, comprising 153 species from 46 families, were documented. There are 112 species classified as trees, six as shrubs, 20 that can be shrubs or small trees, one vine species, 10 palm species, and one grass species. The recorded 43 Philippine endemics and 39 threatened species emphasize the unique riparian flora of Ulot River. Economic uses and seed storage behavior were also assessed through literature and database review. Local communities utilized plant species in the Ulot riparian zone for economic purposes like food (21 species), medicine (61 species), fuelwood (21 species), timber (64 species), landscaping (8 species), dyes/tannins (8 species), and rope-making (4 species), as well as for cultural uses, including ornamentals (15 species), landscaping (8 species), and mastication (2 species). Several species, such as Aquilaria cumingiana, dipterocarps and Syzygium species, are noted to be endemic and have economically important uses. Based on these findings, a conservation framework is proposed that balances sustainable resource use and conservation measures in Samar Island riparian zones. It integrates environmental policies, awareness, and ecotourism while supporting in situ and ex situ conservation, including seed banking and habitat restoration. These strategies are critical in ensuring ecological stability and in local environmental policy-making.